Marginal social groups in Sserbia – a look into the past - Popović, Radomir (Sociološki pregled, 2018)
Vladimir Jovanović: Splendours and miseries of town life - marginal groups and state reaction in Serbia in the 19th century, Zavod za udžbenike, Beograd, 2017, 272 pp.